Coupled cell networks: Boolean perspective - Katarzyna Swirydowicz (Biomath, 2017)
During the 1980s and early 1990s, Martin Golubitsky and Ian Stewart  formulated and developed a theory of "coupled cell networks" (CCNs). Their research was primarily focused onquadrupeds' gaits and they applied the framework of differential equations. Golubitsky and Stewart were particularly interested in change of synchrony between $4$ legs of an animal. For example what happens when the animal speeds up from walk to gallop.